Analysis of Presentation Capabilities and Comparative Study of Domestic and Foreign Adaptations in Attarâs Manteq-o-Teyr - mohamad shahba; tayebeh partovirad (متن شناسی ادب فارسی, 2015)
Attar’s Manteq-o-Teyr (Conference of the Birds) is one of the few works which has found favor with the West in recent decades and, with their special definition of mysticism, has frequently been performed in drama scenes all over the world. In this article, while reviewing the origins of Manteq-o-Teyr, I will compare the adaptations of this mystical poem by authors from outside Iran, Especially Jean-Claude Carrière, with authors from inside of Iran, using descriptive-analytic method. In comparing such adaptations, I will evaluate their strong and weak points based on presentation capabilities and aspects of this poem. The results indicate that by structure, innovation and deconstructing the structural rules of theater and its use of Brecht structure, very close to the narration of Manteq-o-Teyr, in collation with Aristotelian structure, this adaptation has been able to distinguish Carrière theater from the domestic adaptations there are, though, many differences between Manteq-o-Teyr and its adaptations, especially Carrière adaptation, in terms of theme and content. This same gap shows that this work deserves more attention and more serious and effective adaptations. Adaptations, which are indicative of Attar’s thoughts and the Islamic mystical soul of the poem, while applying new theatrical structures as well.